Financial Management Website Design Using a Design Thinking Approach (Case Study Noka Dessert) - Okti Bela Alisia; Moch. Tiofany Yugi Ferdiansyah; Muhammad Alimun; Anisa Hudi Widaningrum; Priska Choirina (Jurnal Teknologi Informasi Universitas Lambung Mangkurat (JTIULM), 2025)
Micro, small and medium enterprises (MSME) such as Noka Dessert often use outdated methods to document financial transactions, which makes tracking finances in real time impossible and is prone to errors. This study intends to explore the creation of a web-based financial management system with the purpose of automating the task of record-keeping and improving real time reporting using the Design Thinking approach. Focusing on users such as owners and employees ensures enhanced accuracy, efficiency, and improved accessibility of the data. The system allows forser authentication as admin and staff, with rights for data entry, validation, and reporting. Functional testing using the System Usability Scale (SUS) has indicated a satisfactory user experience with a mean score of 76. Further research is recommended towards connecting the system with digital payment platforms, overhauling the inventory system, and conducting regular workshops. Noka Dessert is anticipated to improve financial management in this system, leading to sustainable business growth.